n-n=-4(2n-8)+8(n+12)

Simple and best practice solution for n-n=-4(2n-8)+8(n+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-n=-4(2n-8)+8(n+12) equation:


Simplifying
n + -1n = -4(2n + -8) + 8(n + 12)

Combine like terms: n + -1n = 0
0 = -4(2n + -8) + 8(n + 12)

Reorder the terms:
0 = -4(-8 + 2n) + 8(n + 12)
0 = (-8 * -4 + 2n * -4) + 8(n + 12)
0 = (32 + -8n) + 8(n + 12)

Reorder the terms:
0 = 32 + -8n + 8(12 + n)
0 = 32 + -8n + (12 * 8 + n * 8)
0 = 32 + -8n + (96 + 8n)

Reorder the terms:
0 = 32 + 96 + -8n + 8n

Combine like terms: 32 + 96 = 128
0 = 128 + -8n + 8n

Combine like terms: -8n + 8n = 0
0 = 128 + 0
0 = 128

Solving
0 = 128

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 25=a(30-0)(30-60) | | x-56=64 | | -6+3(1-9v)=-24 | | x-32=28 | | 190+b=200b | | (x+5)*28=2x*21 | | 10x-22=8x+12 | | x*ln(x)=(ln(3))/3 | | (x+5)*28=2x+21 | | x^2+y^2-12x+4y=24 | | x+5*28=2x+21 | | s^2+20+4s= | | 4x=44p-16 | | 4m-30+m=3m+4 | | 3(-16+7x)-15x= | | 20*(20+x)=15*(15+3x) | | 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= | | (x*x)=(x-2)*(x+2) | | 21+5=15+11 | | X*12=6*(x+4) | | y=-0.2*36+50 | | 2x+53+68=75 | | k/5-9=-17 | | (x-y+2)-(x+7-2y)= | | s=250+12y | | (x*x)=x-2*x+2 | | y=2*3+2 |

Equations solver categories